KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA DALAM PEMECAHAN MASALAH KALKULUS II - Khoiriyah, Siti (JURNAL e-DuMath, 2016)
Mathematical communication has an important role in mathematics learning for instance, sharpening the way of thinking, improving studentsâ ability in observing the relevance of various mathematics concept, measuring the development of mathematics understanding, and reflecting studentsâmathematics comprehension. For these reasons, it is crucial to know how far studentsâmathematical communiation skills. Therefore, this study aims to describe mathematical communication skills of majors students STKIP MPL. Mathematical communication skills are seen through studentsâanswer analysis in solving Calculus II problem. The research subject consists of three students who get score A, B, dan C. Based on the analysis result found that mathematical communication skills of these subjects are able to communicate mathematical ideas by using pictures and Mathematics symbols. However, they have differences ability in describing and analysing. The first subject is able to describe and analyze pictures precisely. The second subject is not able to describe pictures well, thus the pictures are difficult to understand. While the third subject is able to describe pictures well but can not analyze the picture so the problem solving method is not appropriate. Keywords : mathematical communication skills, problem solving of Calculus II